Seroprevalence of spotted fever group rickettsiae in canines along the United States–Mexico border. (23rd August 2019) - Pieracci, Emily G.; De La Rosa, Juan Diego Perez; Rubio, Daniel Luna; Perales, Mario Eduardo Solis; Contreras, Manuel Velasco; Drexler, Naomi A.; Nicholson, William L.; De La Rosa, José Javier Pérez; Chung, Ida H.; Kato, Cecilia; Barton Behravesh, Casey; Enríquez, María Alejandra Gay; et al.
Abstract: Portions of northern Mexico are experiencing a re‐emergence of Rocky Mountain spotted fever (RMSF), a tickborne disease caused by Rickettsia rickettsii, a member of the spotted fever group of rickettsiae (SFGR) . Infection with R. rickettsii can result in serious and life‐threatening illness in people and dogs. Canine seroprevalence has been used as a sentinel for human RMSF in previous studies. This study aims to quantify SFGR seroprevalence in canines in three northern Mexican states and identify risk factors associated with seropositivity. A total of 1, 136 serum samples and 942 ticks were obtained from dogs participating in government sterilization campaigns and from animal control facilities in 14 Mexican cities in three states. SFGR antibodies were detected using indirect immunofluorescence antibody assays at titre values ≥1/64. Six per cent (69 dogs) showed antibodies to SFGR, with the highest seroprevalence reported in Baja California (12%), Coahuila (4%) and Sonora (4%). Dogs from Baja California had three times higher odds of having SFGR antibodies compared to dogs from Sonora (OR = 3.38, 95% CI, 1.81–6.37). Roughly one quarter (25%) of surveyed dogs were parasitized by ticks ( Rhipicephalus sanguineus sensu lato) at the time of sample collection. A portion of collected ticks were tested for rickettsial DNA using polymerase chain reaction. Positive samples were then sequenced, showing evidence of SFGR including R. massiliae, R. parkeri and R. rickettsii. Dogs that spent the majority of time on the street, such as free‐roaming or community‐owned dogs, showed a greater risk of tick infestation, seropositivity, bearing seropositive ticks, and may play a pivotal role in the spread of SFGR among communities. Estimating the seroprevalence of SFGR in the canine population can help public health campaigns target high‐risk communities for interventions to reduce human RMSF cases.